Marine Microbial Community Composition During the Upwelling Season in the Southern Benguela - Rocke, Emma; Cheung, Shunyan; Gebe, Zimkhita; Dames, Nicole R.; Liu, Hongbin; Moloney, Coleen L. (Frontiers in Marine Science, 2020)
The microbial communities of the southern Benguela upwelling region were sampled quarterly through 1 year, with sampling for prokaryotes taking place in May, September, November and February, spanning the 2015–2016 upwelling season. Picoeukaryote samples were taken in November and February only. Community dynamics were assessed at stations both inside and outside a typical upwelling site. 16S and 18S rRNA amplicon results, respectively, revealed differences in both bacterioplankton and picoeukaryote communities in both space and time (season). There was a significant difference between sites in picoeukaryote community structure and diversity during the upwelling season in February, but not in November. Prokaryote community structure showed significant changes by water type as well as by sampling time or site. The parasitic dinoflagellate, Syndiniales, dominated February samples, and diatoms (Mediophyceae) mostly occurred in November samples, with nitrate driving community structure. Prokaryote results revealed presence of Nitrosopumillus, an ammonium oxidizer, offshore in February. Nitrospina sp., a nitrite oxidizer, was also present in September in hypoxic and deep water samples. This study reveals significant changes in community variability, leading to shifts within interspecies interactions in this region in response to upwelling events. This has far reaching implications with regard to biogeochemical cycling and ecosystem functioning at the microbial level.